IJAR 2019
DOI: 10.21474/ijar01/8830
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Organ Donation in Newly Admitted Students of Medical College: A Case Control Study in Western Maharashtra.

Abstract: Introduction: Organ transplantation is the process of replacing diseased organs, parts of organs or tissues by healthy organs or tissues. The only way to increase organ donations is to educate the health care professionals and public about the importance of becoming an organ donor. One of the best ways is to educate the youngsters in the medical field. Aims: This study aims to determine the knowledge and awareness of 1 st MBBS students regarding organ donation. Material & Methods: Cross sectional questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…24 According to a study in Pune, the awareness on organ donation was raised from 81% to 96% gained after showing an educational film and conducting an interactive session. 25 This was also observed by a study in the USA, that showed that exposure to information on organ donation has positive long term effects with more clinical competency while interacting with patients about infant organ donation. 26…”
Section: Discussionmentioning
confidence: 62%
“…24 According to a study in Pune, the awareness on organ donation was raised from 81% to 96% gained after showing an educational film and conducting an interactive session. 25 This was also observed by a study in the USA, that showed that exposure to information on organ donation has positive long term effects with more clinical competency while interacting with patients about infant organ donation. 26…”
Section: Discussionmentioning
confidence: 62%